2005
DOI: 10.1161/01.str.0000177881.34840.cf
|View full text |Cite
|
Sign up to set email alerts
|

Ischemic Stroke Subtypes and Thrombophilia in Young and Elderly Brazilian Stroke Patients Admitted to a Rehabilitation Hospital

Abstract: Background and Purpose-We sought to examine ischemic stroke subtypes and prevalence of thrombophilia in Brazilian stroke patients. Method-A total of 130 consecutive young and 200 elderly stroke patients were studied. Results-Prevalence of thrombophilia was, respectively: protein S deficiency (11.5% versus 5.5%), protein C deficiency (0.76% versus 1%), resistance to activated protein C (2.3% versus 3.5%), mutation in V

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 8 publications
0
19
0
1
Order By: Relevance
“…These studies also produced conflicting results, with some studies suggesting an association between PTM or FVL and PFO, 24,[41][42][43] and others finding no relation. 21,[37][38][39][40] None of the studies that examined PC, PS, or AT found any association of these deficiencies with PFO and stroke. [37][38][39][40]42 No study has evaluated the utility of warfarin vs antiplatelets for patients with PFO and thrombophilia.…”
Section: Inherited Thrombophilia and Patent Foramen Ovalementioning
confidence: 99%
See 2 more Smart Citations
“…These studies also produced conflicting results, with some studies suggesting an association between PTM or FVL and PFO, 24,[41][42][43] and others finding no relation. 21,[37][38][39][40] None of the studies that examined PC, PS, or AT found any association of these deficiencies with PFO and stroke. [37][38][39][40]42 No study has evaluated the utility of warfarin vs antiplatelets for patients with PFO and thrombophilia.…”
Section: Inherited Thrombophilia and Patent Foramen Ovalementioning
confidence: 99%
“…21,[37][38][39][40] None of the studies that examined PC, PS, or AT found any association of these deficiencies with PFO and stroke. [37][38][39][40]42 No study has evaluated the utility of warfarin vs antiplatelets for patients with PFO and thrombophilia. One small study of 72 patients referred for PFO closure found no difference in recurrent stroke at 6 months in patients with or without thrombophilia.…”
Section: Inherited Thrombophilia and Patent Foramen Ovalementioning
confidence: 99%
See 1 more Smart Citation
“…atrial fibrillation). In studies assessing the role of hereditary thrombophilia in the etiology of cerebral arterial and cerebral venous thrombosis (CAT, CVT), the risk for stroke was found to increase in the presence of different thrombophilic factors [9][10][11][12][13][14][15][16]. Hypercoagulable states are responsible for 5-10% of all IS cases, and hereditary thrombophilia is especially more common in the etiology of IS in the younger subgroup of patients [17].…”
Section: Introductionmentioning
confidence: 99%
“…In Brazil, this genotype frequency is 14.9% and 11.8% in white individuals with stroke and without stroke, respectively; in black individuals, these frequencies are lower, being 10.3% and 1.9% in patients with stroke and without stroke, respectively 28 . According to Carod-Artal et al, 29 the thermolabile MTFHR genotype occurred in 5.05% and 10% of elderly and young individuals with stroke, respectively, admitted to a rehabilitation hospital. On the other hand, it has been shown that the frequency of this genotype is higher in Italy, 30 but paradoxically, cardiovascular complications are estimated to be relatively low.…”
Section: Discussionmentioning
confidence: 99%